2009
DOI: 10.1091/mbc.e09-05-0361
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin Inhibits Tumor Necrosis Factor alpha–induced Nuclear Factor-kappa B Nuclear Translocation via the Novel Mechanism of Decreasing Importin α3 Expression

Abstract: Expression of prohibitin 1 (PHB), a multifunctional protein in the cell, is decreased during inflammatory bowel disease (IBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 41 publications
7
81
0
Order By: Relevance
“…Restoration of colonic epithelial PHB expression using genetic manipulation (villin-PHB transgenic mice) or therapeutic delivery to the colon via nanoparticle or adenovirus protected mice from experimental colitis [43,44]. Our recent data suggest that epithelial PHB sustains anti-oxidant expression [44] and has anti-inflammatory properties such as reducing TNFa-stimulated NF-kB activation [42]. This is in agreement with emerging data that suggest a role of PHB in combating oxidative stress in multiple cells types [39,40,45,46].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Restoration of colonic epithelial PHB expression using genetic manipulation (villin-PHB transgenic mice) or therapeutic delivery to the colon via nanoparticle or adenovirus protected mice from experimental colitis [43,44]. Our recent data suggest that epithelial PHB sustains anti-oxidant expression [44] and has anti-inflammatory properties such as reducing TNFa-stimulated NF-kB activation [42]. This is in agreement with emerging data that suggest a role of PHB in combating oxidative stress in multiple cells types [39,40,45,46].…”
Section: Introductionsupporting
confidence: 88%
“…We have previously shown that expression of PHB protein is reduced in mucosa during active inflammatory bowel disease and in Caco2-BBE cells treated with TNFa or exogenous oxidants [37,42]. It has been demonstrated that TNFa and IFNc induce autophagy in intestinal epithelium [31,55] and that autophagy can attenuate inflammatory responses, thereby maintaining intestinal homeostasis [56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations